Mercenaries in the Galician Army of the Western Ukrainian National Republic - Stetsyshyn, Oleh (East/West)

(untitled) (Canadian Institute of Ukrainian Studies University of Alberta, 2022)
In 1918 Central and Eastern Europe were on the brink of enormous change. The collapse of the German and Austro-Hungarian empires had led to the growth of national self-awareness in many peoples, and the Czechs, Poles, Hungarians, and peoples of the Baltic and Balkan regions declared their nation-statehood. Ukrainians also exercised their right to self-determination, establishing the Western Ukrainian National Republic (Ukr. acronym: ZUNR) on their ethnic territory. The regular military force of the new republic was the Galician Army, with the word “Ukrainian” subsequently added to it (Ukr. acronym: UHA). It immediately commenced armed operations against Polish formations that also aimed to seize power in this territory. However, when establishing their army the Ukrainians encountered serious personnel issues, especially a severe shortage of Ukrainian officers. One means of resolving this problem was to contract military personnel of other nationalities who were citizens of the ZUNR as well as other countries. In some cases actual mercenaries were hired. This article describes where, how, and under what conditions this took place in the UHA.